The Influence of Price/Earning Ratio (PER), Price to Book Ratio (PBR) and Price to Sales Ratio (PSR) on Net Asset Value (NAV) in Sharia Equity Fund - Tanius, Gerry Immanuel; Widjojo, Rosita (Jurnal Manajemen dan Bisnis Indonesia, 2018)
From many kinds of investment in Indonesian capital markets, a mutual fund is one of the instrument to be discussed. Within a short time, the mutual fund gives a significant influence to the Indonesian capital markets. A mutual fund is one of the alternatives for the investors, especially for small investors or for the investor that does not want to meet high risk. In the growing of Indonesian capital markets, the net asset value (NAV) of the mutual fund should be increasing, and the increase of the NAV proves it. The sharia equity fund is no different. As an alternative investment, the sharia mutual fund in Indonesia is growing; however, it does not seem attractive to the investor, reflected by the small weighting from the mutual fund industry. The reason why investors are reluctant to invest in sharia equity fund is the volatility, compared to the conventional equity fund. To guide investors and to attract investment in sharia equity funds, some indicators can be used, such as PER, PBR and PSR. This study will use these indicators as the independent variables: PER (X1), PBR (X2) and PSR (X3) on the Net Asset Value (NAV) as the dependent variable (Y)  in sharia equity fund using the Jakarta Islamic Index (JII) data. In this research, the researcher uses a quantitative method using secondary data. The results show that there is a significant influence of PER, PBV and PSR on NAV in sharia equity funds. As a consequence, PER, PBR and PSR can guide investors’ decisions to invest in sharia mutual fund.   Keywords: PER, PBR, PSR, NAV, sharia mutual fund